Identification of serum miRNAs as novel non-invasive biomarkers for detection of high risk for early gastric cancer - Shiotani, A; Murao, T; Kimura, Y; Matsumoto, H; Kamada, T; Kusunoki, H; Inoue, K; Uedo, N; Iishi, H; Haruma, K (British journal of cancer, 2013)
Background: Many micro-RNAs (miRNAs) are differentially expressed in Helicobacter pylori -infected gastric mucosa and in gastric cancer tissue and previous reports have suggested the possibility of serum miRNAs as complementary tumour markers. The aim of the study was to investigate serum miRNAs and pepsinogen levels in individuals at high risk for gastric cancer both before and after H. pylori eradication. Methods: Patients with recent history of endoscopic resection for early gastric cancer and the sex- and age-matched controls were enrolled. Serum was collected from subjects before or after eradication and total RNA was extracted to analyse serum levels of 24 miRNAs. Serum pepsinogen (PG) I and II levels were measured using enzyme-linked immunosorbent assay kits. Results: Using miR-16 as an endogenous control, the relative levels of miR-106 and let-7d before and after H. pylori eradication and miR-21 after eradication were significantly higher in the high-risk group than in the controls. H. pylori eradication significantly decreased miR-106b levels and increased let-7d only in the control group. After eradication, the combination MiR-106b with miR-21 was superior to serum pepsinogen and the most valuable biomarker for the differentiating high-risk group from controls. Conclusion: Serum miR-106b and miR-21 may provide a novel and stable marker of increased risk for early gastric cancer after H. pylori eradication.